Efficient strengthening technique for reinforced concrete slabs - SFRC and CFRP laminate strips - Bonaldo, Everaldo (2006)
A promising strengthening strategy, using carbon fiber reinforced polymer (CFRP) materials, consists in applying CFRP laminate strips into pre-cut slits opened in the concrete cover of the elements to strengthen. This strengthening technique is designated by Near Surface Mounted (NSM) and has been successfully used to increase the flexural and the shear resistance of concrete and masonry structures. The present work describes an efficient strategy, using steel fiber reinforced concrete (SFRC) and NSM CFRP laminates, for the strengthening of existing reinforced concrete (RC) slabs. The use of a SFRC compression overlay can provide the necessary ductility for attaining high level of tensile stress in the CFRP strengthening system and therefore preventing the concrete crushing failure mode. In the present work, the effectiveness of this technique to increase the service and ultimate load carrying capacity of RC slabs is assessed by an experimental program. A numerical strategy was developed to predict the load-deflection relationship of this type of elements. The results are presented and analyzed, and the performance of the numerical model is appraised.